Comparing contiguous high- and low-elevation continental margins: New (U-Th)/He constraints from South Brazil and an integration of the thermochronological record of the southeastern passive margin of South America - Hueck, Mathias; Dunkl, István; Oriolo, Sebastián; Wemmer, Klaus; Stipp Basei, Miguel Angelo; Siegesmund, Siegfried (Tectonophysics)
The southeastern coast of South America is an example of the complexity of passive continental margins, as it displays both high- and low-elevation segments despite sharing a similar pre-rift geological history and structural configuration. As such, it is a prime candidate for investigating debated questions concerning the evolution of passive margins, such as the tectonic mechanisms driving uplift, their relationship to rifting and continental break-up, and why some margins are elevated when others are not. In this contribution, we present new (U-Th)/He data from a low-altitude portion of the South American passive margin in South Brazil, the Sul-rio-grandense Shield, and interpret it in the context of the regional thermochronological record. New results produce widespread apparent ages and reveal a complex exhumation history from the early Paleozoic onwards, including reheating during Paleo-Mesozoic sedimentation. For most of the study area, however, final exhumation was achieved at the latest during the rifting and early opening of the South Atlantic Ocean (135 Ma to 100 Ma). In spite of the presence of major Neoproterozoic shear zones, the inherited NE-SW structural framework seems not to have strongly influenced the thermochronological record. The new data were integrated into a large compilation of apatite fission track and (U-Th)/He results from southeast South America, in order to compare regional trends and investigate possible tectonic controls in the exhumation history. Low-elevation areas of the passive margin consistently record complex pre-rift cooling histories, while high-elevation areas experienced significant Upper Cretaceous/Paleogene uplift associated with the reactivation of Neoproterozoic shear zones. Because the inherited structural features of both segments are similar, plate dynamics alone cannot be responsible for the variating response. Hence, mantellic processes associated with post-rift alkaline magmatism may have affected the contrasting exhumation histories. This process was ...